(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
There are three main types of tourism in Uzbekistan: inbound, outbound and domestic tourism. Inbound and domestic tourism include the main and specialized tourist products: excursions to tourist attractions; accommodation in hotels, recreation areas, resorts, sanatoriums, tourist villages, home camps, camps; tasting national cuisine and wines; participation in festivals and festive events; convenient movement around the country.